2019
DOI: 10.1111/eje.12448
|View full text |Cite
|
Sign up to set email alerts
|

Graduate mobility: Where do dentistry graduates choose to practise?

Abstract: Background and objective The international higher education market has grown and developed rapidly. International students generate attractive income for host universities, and gaining an international education benefits students in an increasingly globalised world. However, there is little research regarding where international students intend to work and settle beyond graduation. This study investigated where dentistry students intended to practise after graduation, and whether international students who gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Further study findings revealed that compared to NZ‐educated DHs, more Swedish‐educated DHs preferred to stay and work within their own country than going overseas. Firstly, more international students were enrolled in the NZ study programmes, some of whom choose to go back to their home country to work upon graduation 10 . Secondly, DHs need to be fluent in the language of the country in which they work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further study findings revealed that compared to NZ‐educated DHs, more Swedish‐educated DHs preferred to stay and work within their own country than going overseas. Firstly, more international students were enrolled in the NZ study programmes, some of whom choose to go back to their home country to work upon graduation 10 . Secondly, DHs need to be fluent in the language of the country in which they work.…”
Section: Discussionmentioning
confidence: 99%
“…In NZ, dental hygienists are mainly employed in private dental practices and can treat patients of all ages while dental therapists treat children under the age of 18, mainly within the public domain of district health boards (DHBs) 2,7 compared to Sweden where dental hygienists provide care for people of all ages, in both the private and public sectors. In both countries, oral health for children and adolescents is state‐funded, while adult patients pay a fee for service 8‐10 . Different fee schemes allow certain patient categories to receive subsidized state‐funded care.…”
Section: Introductionmentioning
confidence: 99%
“…First and foremost, they are eager to experience new ways of thinking and acting in their field of study. Next to that, studying abroad enhances career opportunities following the acquisition of improved experiences for future employment in their home country or other nations [4] . Additionally, more often than not, international students receive a broader and more flexible education than they receive in their home country.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [13] reveals that the proportion of graduated medical talents in Kazakhstan is less than 50%, which is unable to meet the shortage of medical talents, and proposes to build a platform for tracking the employment of graduated medical graduates and improve the auxiliary services for employment support. Literature [14] investigated the employment intention of international dental students and found that the proportion of international dental graduates who stayed back to New Zealand for employment has gradually declined since 2001, which provides some information reference for the talent management department of the home country. Literature [15] describes two professional development programs related to the agricultural profession, which aim to improve the prospective graduates, professional practice skills related to the profession, as well as the ability to collaborate and communicate with others, which promotes the prospective graduates' professional practice skills and sense of self-development.…”
Section: Introductionmentioning
confidence: 99%